ANALISIS KUALITAS MATERI PENGAJIAN DI MAJELIS TA'LIM: STUDI KASUS DI KABUPATEN PADANG LAWAS - Mhd. Hasbin Daulay; Qomariyah (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
Non-formal Islamic educational institutions that play an important role in improving the quality of religion in Indonesia are the ta'lim councils. This research aims to identify the activities that the community participates in while participating in the ta'lim assembly. To facilitate research, the author used qualitative methods with interview techniques to obtain information from informants. The research results show that the ta'lim assembly has a big role for the community in the learning activities within it. There are two types of activities carried out based on this research. First, in the field of education, people learn to read the Koran, learn how to practice prayer, lead tahlil, and memorize prayers after prayer. Second, in social activities, the community participates in food sharing activities, Friday blessings, social service, mass circumcisions, as well as sharing takjil and fasting together during the month of Ramadan.